Experimental Study of the Quality of Geopolymer Concrete with Wood Powder - Yayan adi Saputro; Muhammad Daffa Nabil Ifaani; Fiki Nur Fitriani (PT FORMOSA CENDEKIA GLOBAL, 2023)
With the development of technology in the field of materials engineering, experts are working on existing problems in the field of construction. One of them uses eco-friendly waste as another alternative material and can be used as a substitute for cement in concrete mixes. The concrete mix produced is environmentally friendly as it uses industrial waste to completely replace cement. Concrete mixtures are known as geopolymers. . This geopolymer concrete can be formed from raw materials containing many silica and aluminum elements. These elements are found in many industrial wastes, including fly ash. And many other wastes in use today are not used as substitutes for fly ash, but as additives. One such waste is sawdust. Waste from mechanical or manual cutting of wood. The lumber industry inevitably produces wood waste in the form of sawdust and chips. One solution is to turn this waste into value-added products using simple technology. One of them is the mixture used to make geopolymer design